Interplay of Various Evolutionary Modes in Genome Diversification and Adaptive Evolution of the Family Sulfolobaceae - Banerjee, Rachana; Chaudhari, Narendrakumar M.; Lahiri, Abhishake; Gautam, Anupam; Bhowmik, Debaleena; Dutta, Chitra; Chattopadhyay, Sujay; Huson, Daniel H.; Paul, Sandip (Frontiers in Microbiology, 2021)
Sulfolobaceae family, comprising diverse thermoacidophilic and aerobic sulfur-metabolizing Archaea from various geographical locations, offers an ideal opportunity to infer the evolutionary dynamics across the members of this family. Comparative pan-genomics coupled with evolutionary analyses has revealed asymmetric genome evolution within the Sulfolobaceae family. The trend of genome streamlining followed by periods of differential gene gains resulted in an overall genome expansion in some species of this family, whereas there was reduction in others. Among the core genes, both Sulfolobus islandicus and Saccharolobus solfataricus showed a considerable fraction of positively selected genes and also higher frequencies of gene acquisition. In contrast, Sulfolobus acidocaldarius genomes experienced substantial amount of gene loss and strong purifying selection as manifested by relatively lower genome size and higher genome conservation. Central carbohydrate metabolism and sulfur metabolism coevolved with the genome diversification pattern of this archaeal family. The autotrophic CO2 fixation with three significant positively selected enzymes from S. islandicus and S. solfataricus was found to be more imperative than heterotrophic CO2 fixation for Sulfolobaceae. Overall, our analysis provides an insight into the interplay of various genomic adaptation strategies including gene gain–loss, mutation, and selection influencing genome diversification of Sulfolobaceae at various taxonomic levels and geographical locations.